Impact of the Cooking Methods on the Tempeh Nutritional Composition. (7th June 2021) - Castanheira, Isabel; Serodio, Ana; Nascimento, Ana; Gueifao, Sandra; Santiago, Susana; Assunção, Ricardo; Barbosa, Cassia
Abstract: Objectives: Promoting plant-based protein diets (PBPDs) is of utmost importance in public health nutrition. However, the studies on the nutrient profile of PBPDs for foods as consumed remain scare. Tempeh is a fermented vegetable food used as an alternative source of protein in plant-based and flexitarian diets. This study aims to: 1) compare the nutritional profile of "raw" tempeh available in Portugal (PT) and in the USA (according to data available at the USDA); 2) assess the impact of different cooking methods on the nutritional composition of tempeh. Methods: Three pools (with 20 samples of 6 commercial brands – most consumed brands) of tempeh were analyzed, one "raw" and two cooked (sautéed and stewed). AOAC methods determined the macronutrient protein profile, total sugars and fat, Fe, Zn, Mg, Ca, P, Na and K by ICP-OES, and Cu Mn and Se by ICP-MS. Results: Comparing with the tempeh values (IFDC 174272) from the USDA table, the "raw" tempeh from Portugal presents, in general, lower values for all parameters analyzed, except for carbohydrates, Na and Cu, which value are higher, and Se, which value is similar. Comparing the different cooking methods in PT tempeh, there are statistically significant differences (p < 0.05) between the sautéed and the stewed for Fe, Zn, Mg, Ca, P, K and Mn; there are statistically significant differences (p < 0.05) between the "raw" and the stewed sample for Na, Cu and Se; and there are no statistically significant differences (p > 0.05) between proteins, fats and total sugars for any of the cooking methods. Conclusions: The results showed that the nutritional composition of tempeh presents differences when its origin is PT or USA. Additionally, these results showed that the cooking method used determines the nutritional composition of this product, in terms of micronutrients. Important aspects such as the retention factors of these foods and the bioaccessibility of their components should deserve attention in future studies, especially when different cooking methods are considered. Funding Sources: This work was completed under the METROFOOD-PP project frame and received funding from the European Union's Horizon 2020 research and innovation program under grant agreement No 871083.